Heritability estimates of tree dryness and correlation with latex parameters in Hevea brasiliensis - Omokhafe K O; Aniamaka E E (Journal of the Rubber Research Institute of Sri Lanka, 2000)
Eleven clones of Hevea brasiliensis were evaluated for incidence of tree dryness and four latex parameters at three locations. There was significant clonal variation in incidence of tree dryness with heritability estimates of 0.08 and 0.05 in two locations. Contingency test of tree dryness and the four latex parameters viz. initial volume, final volume, initial flow rate and plugging index was significant with significant correlation between tree dryness and initial volume, final volume and initial flow rate. The breeding and agronomic implications of low heritability of tree dryness and significant correlation with three latex parameters are discussed.
Keywords: Heritability; Latex parameters; Root stock; Tree dryness